Amelioration de la production laitiere en vue de satisfaire la demande croissante des consommateurs en Afrique subsaharienne - Rey, B.; Thorpe, W.R.; Smith, Jimmy W.; Shapiro, Barry I.; Osuji, P.O.; Mullins, G.; Agyemang, K. (CIPEA, 1994)
This document is based on the deliberations and outputs of two ILCA in-house workshops held in 1992, and of numerous individual contributions by ILCA scientists. This work has similarities with the ILCA project on smallholder market-oriented dairying. Factors influencing development of market-oriented smallholder dairying in SSA, and factors affecting farm productivity in dairying are listed. The objectives and methods of the four phases, viz, typification of dairy system, characterization of a specific dairy system, seeking ways to enhance the development of specific dairy systems and cross-site synthesis are described.